Narrative strategies in live-streaming commerce: host storytelling, immersion, and impulse buying - Wang, Mengdi; Zhang, Wenjing; Li, Yanxia (Frontiers in Psychology, 2026)
Live-streaming hosts play a pivotal role in e-commerce, yet their narration strategies remain underexplored. This study develops a framework to examine how host narration strategies influence consumers’ impulsive buying behavior. The exploratory phase involved textual analysis of host narration, which informed the conceptual model grounded in Narrative Transportation Theory. In the confirmatory phase, 398 user responses were examined using structural equation modeling (SEM) to test the path model and fuzzy set qualitative comparative analysis (fsQCA) to identify sufficient configurations of influencing factors. Results show that emotional persuasion, narrative presence, and immersion are consistently associated with impulsive buying, while interactive engagement, time pressure, and accuracy have context-specific effects. These findings emphasize the need to adapt live-streaming strategies flexibly to match consumer characteristics and situational contexts, offering actionable insights for enhancing consumer engagement and purchase behavior in live-streaming commerce.